EDUCATION AND TRAINING REGARDING MENSTRUAL HYGIENE MANAGEMENT (MHM) AS AN EFFORT TO CARE REPRODUCTIVE ORGANS IN ADOLESCENT - Mira Triharini; Aria Aulia Nastiti; Ni Ketut Alit Armini; Iqlima Dwi Kurnia; Praba Diyan Rachmawati; Ilya Krisnana; Arik Setyani; Ananda Hanna Pratiwi (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2022)
Introduction: According to the Indonesian Demographic and Health Survey (IDHS) in 2017, young women (63.9%) in maintaining cleanliness during menstruation are still lacking due to low knowledge and information about personal hygiene during menstruation. SMP Negeri 1 Sampit is located in Central Kalimantan where most of the students do not have knowledge about menstrual hygiene management. Methods: The activities used in this community service program were in the form of health education to 120 students of 7th and 8th grades. The community service events carried out through this webinar include opening, pretest, giving material, and closing with a post test. The pretest was carried out before giving the material to determine the participant's initial understanding of menstrual hygine management. Results: Knowledge related to adolescent growth and development scored well as many as 19 people (15.83%) then during the good posttest it became 63 people (52.50%). Knowledge related to menstrual hygiene management during the pretest who got a good score was only 20 people (16.67%) and 72 people (60%) good in posttest. While the knowledge related to mood disorders in adolescents who got a good score at the pretest was 21 (17.5%) and 70 people (58.3%) had a good score in posttest. Conclusion: Community service activities conducted in the form of online webinars to provide health education and modules to teachers can improve knowledge and practice of menstrual hygiene management as an early effort in maintaining and caring for the health of the female reproductive organs.